Identifikasi Bahan Kimia Obat dalam Sediaan Jamu Pegal Linu Menggunakan Metode Spektroskopi Inframerah - Odilia Dea Christina; Sandi Mahesa Yudhantara; Ayu Ina Solichah; Atalia Tamo Ina Bulu (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Pegel linu herbal medicine is one of the traditional remedies widely consumed by the community to relieve pain and fatigue. The high market demand, particularly through online marketplaces, has the potential to be misused by irresponsible producers by illegally adding pharmaceutical chemicals to enhance therapeutic effects. This study aimed to identify the presence of pharmaceutical adulterants, namely paracetamol, sodium diclofenac, and dexamethasone, in peg el linu herbal medicines circulating in the market using Fourier Transform Infrared (FTIR) spectroscopy. Ten herbal medicine samples were selected using purposive sampling based on criteria such as the absence of distribution permit numbers or the presence of exaggerated therapeutic claims. The samples were prepared through extraction procedures and analyzed using FTIR-ATR by comparing the sample spectra with reference standards. The results showed that one sample tested positive for paracetamol and one sample tested positive for dexamethasone, while sodium diclofenac was not detected in any of the samples. The presence of pharmaceutical adulterants was identified based on the appearance of characteristic functional groups such as O–H, N–H, and C=O at specific wavenumbers. These findings indicate that some peg el linu herbal medicines circulating in the market still contain illegal pharmaceutical adulterants, which may pose potential health risks to consumers.